Improving students' arabic reading skills through cooperative learning strategy type team games tournament - Ikke Wulan Dari; Nova Asvio (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
This study aims to help students overcome problems in learning in order to achieve the desired learning outcomes. This research is classroom action research (CAR), using three cycles for six meetings. From the results of the first cycle, it can be seen that the average student test results were 63.96. In the second cycle, the average score of the students' test results was 64.69, in the second cycle, learning mastery increased 33.34% from the initial data. In cycle III seen from the average value of the test results of students is 77.52, students who achieve completeness are 25 people with a percentage of 83.33%, while students who have not completed reach 5 students with a percentage of 16.66%, in Cycle III learning completeness increased by 13.33% from the initial data. It was concluded that the cooperative learning type TGT strategy could improve Arabic reading skills of class VIII C students at SMP Muhammadiyah I Kalirejo Central Lampung with very good results.